Pheromones modulate reward responsiveness and non-associative learning in honey bees - Baracchi, David (Sci Rep, 2017)
Pheromones are chemical messengers that trigger stereotyped behaviors and/or physiological processes in individuals of the same species. Recent reports suggest that pheromones can modulate behaviors not directly related to the pheromonal message itself and contribute, in this way, to behavioral plasticity. We tested this hypothesis by studying the effect of pheromones on sucrose responsiveness and habituation in honey bees. We exposed workers to three pheromone components: geraniol, which in nature is used in an appetitive context, and isopentyl acetate (IPA) and 2-heptanone (2H), which signal aversive situations. Pheromones associated with an aversive context induced a significant decrease of sucrose responsiveness as 40% and 60% of bees exposed to IPA and 2H, respectively, did not respond to any sucrose concentration. In bees that responded to sucrose, geraniol enhanced sucrose responsiveness while 2H, but not IPA, had the opposite effect. Geraniol and IPA had no effect on habituation while 2H induced faster habituation than controls. Overall, our results demonstrate that pheromones modulate reward responsiveness and to a lower degree habituation. Through their effect on sucrose responsiveness they could also affect appetitive associative learning. Thus, besides conveying stereotyped messages, pheromones may contribute to individual and colony-level plasticity by modulating motivational state and learning performances.